2017
DOI: 10.1186/s40795-017-0141-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary intake and BMI among newly diagnosed type 2 diabetes patients attending diabetic clinics in Kampala

Abstract: Background: Dietary intake is a known determinant of body mass index (BMI) among different populations and is therefore a useful component for BMI control. To our knowledge, no study has investigated the usual dietary intake and its association with BMI in type 2 diabetes patients among the Ugandan population. This study aimed to analyse the usual dietary intake of newly diagnosed type 2 diabetes patients and determine the association between the different dietary nutrients and BMI. Methods: We conducted a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(41 reference statements)
1
4
2
Order By: Relevance
“…In the adjusted analysis, a higher carbohydrate intake was significantly associated with lower BMI in the present study. Contrary to our study, another study from Uganda reported the association between higher intake of carbohydrates and higher BMI [ 23 ]. However, substantial evidence revealed an inverse relationship of carbohydrate intake with BMI and waist circumference, similar to our study results [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the adjusted analysis, a higher carbohydrate intake was significantly associated with lower BMI in the present study. Contrary to our study, another study from Uganda reported the association between higher intake of carbohydrates and higher BMI [ 23 ]. However, substantial evidence revealed an inverse relationship of carbohydrate intake with BMI and waist circumference, similar to our study results [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Median intakes of nutrients were presented along with two-sided p values for Mann–Whitney and Kruskal–Wallis tests of significance. Moreover, to establish the associations between dietary intakes and anthropometric measurements (BMI, waist circumference, and WHR as continuous variables), energy-adjusted measures of nutrient intakes (proteins, carbohydrates, and fats) were applied through nutrient density models [ 23 ]. Additionally, carbohydrate intake (energy-adjusted) was used for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…According to the findings of the present study, both BMI and HbA 1C were associated with carbohydrate intake. This fact has been well reported in most of the investigations carried out among the diabetic population (Haimoto et al, 2009; Matovu et al, 2017; Haimoto et al, 2018; Yamakawa et al, 2019). Increasing evidence suggests that carbohydrate is the most important determinant of postprandial blood glucose levels.…”
Section: Discussionsupporting
confidence: 63%
“…Interventions to maintain optimal body mass index (BMI), glycemic control, and insulin resistance are the cornerstones of the management of T2DM. Several prospective studies carried out in different settings in other countries have reported various associations of dietary intake with BMI and the glycemic state as assessed via HbA 1C and fasting plasma glucose (FPG) concentration in patients with T2DM (Lee et al, 2012; Velázquez‐López et al, 2016; Matovu et al, 2017). However, data focused on dietary intake and its' associations with BMI and glycemic profile in diabetic patients is still unexplored in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence in Uganda shows a high rate of overweight among T2DM patients. 8 Unfortunately, the specific composition of this bodyweight remains largely unknown. We are unsure whether it is fat mass or fat-free mass compartments.…”
Section: Introductionmentioning
confidence: 99%